1, 2, 4-Triazole-based molecular switches: crystal structures, Hirshfeld surface analysis and optical properties. Issue 38 (6th June 2016) - Safin, Damir A.; Robeyns, Koen; Garcia, Yann
Abstract : A series of eight closely related N -salicylidene-4-amino-1, 2, 4-triazole compounds has been prepared. Their crystal structures were elucidated by single-crystal X-ray diffraction and optical properties were examined by diffuse reflectance spectroscopy. Noncovalent interactions detected in these compounds were, for the first time, analyzed by means of Hirshfeld surface analysis. Abstract : We have studied a series of eight closely related N -salicylidene-4-amino-1, 2, 4-triazole molecules1–8, obtained by condensation of the corresponding aldehyde with 4-amino-4 H -1, 2, 4-triazole. 1 H NMR spectroscopy in solution revealed the presence of a single structure at least in DMSO- d 6 . According to single-crystal X-ray diffraction, it was established that the crystal structures of5–8 each are stabilized by a linear intramolecular hydrogen bond of the O–H⋯N type, formed between the o -OH hydrogen atom of the phenolic ring and the imine nitrogen atom. The same o -OH function in the crystal structures of1–4 was found to be involved in the intermolecular hydrogen bonds with one of the triazole nitrogen atoms of the adjacent molecule. The overall geometry of each molecule in the structures of1–8 was found to be almost planar or slightly deviated from planarity. Hirshfeld surface analysis showed that the structures of all compounds are mainly characterized by H⋯H, H⋯C, H⋯N and H⋯O contacts but some contribution from C⋯C and C⋯N contacts is also clearly observed. Diffuse reflectance spectroscopy reveals the exclusive presence of the enol form in the solid state at room temperature for1–6 and8, while a mixture of dominant enol and cis -keto forms were found for7 . All the studied molecules1–8 were not photoswitchable, while7 was found to be thermochromic from coloured to colourless upon cooling.